Association between Nonalcoholic Fatty Liver Disease at CT and Coronary Microvascular Dysfunction at Myocardial Perfusion PET/CT - Vita, Tomas (Radiology, 2019)
BACKGROUND: Cardiovascular disease is a major cause of mortality in patients with nonalcoholic fatty liver disease (NAFLD). However, the association of NAFLD with coronary microvascular dysfunction is, to our knowledge, unknown. PURPOSE: To determine whether coronary microvascular dysfunction is more prevalent in patients with NAFLD and to determine whether coronary microvascular dysfunction predicts major adverse cardiac events (MACE) independently of NAFLD. MATERIALS AND METHODS: This retrospective study (2006–2014) included patients without evidence of obstructive epicardial coronary artery disease and healthy left ventricular ejection fraction (≥40%) at a clinical rest and stress myocardial perfusion PET/CT. NAFLD was defined by a mean hepatic attenuation of less than 40 HU at CT and coronary microvascular dysfunction as a coronary flow reserve (CFR) of less than 2.0. A composite of all-cause mortality, myocardial infarction, coronary revascularization, and hospitalization because of heart failure comprised MACE (130 of 886 patients; 14.7%). The relation between NAFLD and MACE was assessed by using multivariable Cox regression analysis. RESULTS: Among 886 patients (mean age, 62 years ± 12 [standard deviation]; 631 women [mean age, 62 years ± 12 years] and 255 men [mean age, 61 years ± 12]; and ejection fraction, 63% ± 9), 125 patients (14.1%) had NAFLD and 411 patients (46.4%) had coronary microvascular dysfunction. Coronary microvascular dysfunction was more prevalent (64.8% vs 43.4%; P < .001) and CFR was lower (1.9 ± 1.1 vs 2.2 ± 0.7; P < .001) in patients with NAFLD compared with those without NAFLD. NAFLD independently predicted coronary microvascular dysfunction (P = .01). The interaction of NAFLD and male sex predicted MACE (hazard ratio, 1.45; 95% confidence interval: 1.08, 1.69; P = .008) and coronary microvascular dysfunction remained associated with MACE (adjusted hazard ratio, 1.46; 95% confidence interval: 1.02, 2.07; P = .04). CONCLUSION: Coronary microvascular dysfunction was more prevalent in patients with nonalcoholic fatty liver disease and predicted major adverse cardiac events independently of nonalcoholic fatty liver disease. © RSNA, 2019 Online supplemental material is available for this article. See also the editorial by Ambale-Venkatesh and Lima in this issue.